2016
DOI: 10.1039/c6ra19653e
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the photoinduced electron injection processes for natural dye-sensitized solar cells: the impact of anchoring groups

Abstract: In this study, nine different natural dyes having various anchoring groups were extracted from various plants and used as photo-sensitizers in DSSC applications. The photovoltaic parameters were investigated as a function of these anchoring groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…The inset of Figure a shows the absorption spectra of wheat and chickpea DNA in aqueous solutions at ≈260 nm, because of the absorption of aromatic base molecules in its skeleton . The difference in their absorption intensity can be mainly attributed to two factors which are as follows: (i) length of DNA molecule: W (≈100.000 genes) has longer DNA chains than C (≈28 000 genes) and (ii) character of DNA molecule: W (≈13.000 Mbp) has more alkyl group hosted adenine bases than C (≈750 Mbp) As is well‐known, longer alkyl chains enable densely packed adsorption of dye molecules, which passivate well on the surface and/or interior trap states of TiO 2 . Moreover, the long alkyl chain is believed to repel iodide from the TiO 2 surface, and thus, reduce the recombination rate.…”
Section: Resultsmentioning
confidence: 99%
“…The inset of Figure a shows the absorption spectra of wheat and chickpea DNA in aqueous solutions at ≈260 nm, because of the absorption of aromatic base molecules in its skeleton . The difference in their absorption intensity can be mainly attributed to two factors which are as follows: (i) length of DNA molecule: W (≈100.000 genes) has longer DNA chains than C (≈28 000 genes) and (ii) character of DNA molecule: W (≈13.000 Mbp) has more alkyl group hosted adenine bases than C (≈750 Mbp) As is well‐known, longer alkyl chains enable densely packed adsorption of dye molecules, which passivate well on the surface and/or interior trap states of TiO 2 . Moreover, the long alkyl chain is believed to repel iodide from the TiO 2 surface, and thus, reduce the recombination rate.…”
Section: Resultsmentioning
confidence: 99%
“…Another work by a different research group revealed that long-hydroxyl and carbonyl-chain bearing anthocyanin generates maximum electron transfer rate (k 3T ) and results in the highest efficiency of 1.87% for anthocyanin with a concentration of 1 g dye per 10 mL water. 24 The use of pomegranate dye has been reported by Ghann et al, which successfully narrowed the band gap, and as a result, the power conversion efficiency of 2.0% was obtained. 11 The use of four synthetic environment-friendly avylium salts as anthocyanin-like sensitizers has been reported by Calogero et al 25 In our previous work, we investigated the pigments of single and combined cyanidin-3-O-glucoside and peonidin-3-Oglucoside with a concentration of 2.0 mM and pH 2.0.…”
Section: Introductionmentioning
confidence: 96%
“…Previously many natural dyes have not been the promising candidates in terms of efficiency but dyes extracted from yellow‐flamboyant and A. amantacea have competitive efficiency with some inorganic dyes. [ 17–19 ]…”
Section: Introductionmentioning
confidence: 99%